High concentrations of divalent cations isolate monosynaptic inputs from local circuits in the auditory midbrain - Sivaramakrishnan, Shobhana; Sanchez, Jason; Grimsley, Calum (Frontiers in Neural Circuits, 2013)
Hierarchical processing of sensory information occurs at multiple levels between the peripheral and central pathway. Different extents of convergence and divergence in top down and bottom up projections makes it difficult to separate the various components activated by a sensory input. In particular, hierarchical processing at sub-cortical levels is little understood. Here we have developed a method to isolate extrinsic inputs to the inferior colliculus (IC), a nucleus in the midbrain region of the auditory system, with extensive ascending and descending convergence. By applying a high concentration of divalent cations (HiDi) locally within the IC, we isolate a HiDi-sensitive from a HiDi-insensitive component of responses evoked by afferent input in brain slices and in vivo during a sound stimulus. Our results suggest that the HiDi sensitive component is a monosynaptic input to the IC, while the HiDi-insensitive component is a local polysynaptic circuit. Monosynaptic inputs have short latencies, rapid rise times and underlie first spike latencies. Local inputs have variable delays and evoke long-lasting excitation. In vivo, local circuits have variable onset times and temporal profiles. Our results suggest that high concentrations of divalent cations should prove to be a widely useful method of isolating extrinsic monosynaptic inputs from local circuits in vivo.